Perbedaan Efektivitas Konsumsi Jus Pisang Ambon Dan Jus Kiwi Terhadap Penurunan Hipertensi Pada Lansia : Differences Of The Effectiveness Of The Consumption Of Ambon Banana Juice And Kiwi Juice Towards Reducing Hypertension In The Elderly - Ni Kadek Okta Pramesti Dewi, Ni Kadek Okta Pramesti Dewi (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Elderly is a process experienced by humans from the beginning and naturally proceeds which indicates humans have passed through three stages, namely, children, adults, and the elderly. According to the American Society of Hypertension (ASH) hypertension is a progressive collection of cardiovascular symptoms as a result of other complex and interrelated conditions. Ambon bananas contain a lot of fiber so that potassium, magnesium, and calcium contained in Ambon bananas can be well absorbed by the body so that they can lower blood pressure. Kiwi fruit is a fruit that contains vitamin C and potassium to maintain blood pressure conditions and heart health.  Methods: This type of research uses a quasi-experimental research design using a two group’s pretest-posttest design. The sampling technique used is random sampling. The sample in this study amounted to 30 elderly respondents with hypertension.  Results: Univariate results showed that in the ambon banana juice group before the intervention, 2 people (13.3%) had mild blood pressure, 13 people (86.7%) had moderate blood pressure, after the intervention, 1 person (6.7%) had normal blood pressure, 13 people (86.7%) had mild blood pressure, 1 person (6.7%) had moderate blood pressure. In the kiwi juice group before the intervention, 15 people (100%) had moderate hypertension, after the intervention 8 people (53.3%) had mild hypertension, and 7 people (46.7%) had mild blood pressure. The results of the Wilcoxon bivariate test in the ambon banana group obtained a p-value 0.001 < 0.05, while in the kiwi fruit group p-value of 0.002 < 0.05 means that there is an effect of consumption of ambon banana juice and kiwi juice on reducing hypertension in the elderly. The Mann-Whitney test yielded a p-value of 0.017 < 0.05, then Ha was accepted and Ho was rejected, this indicates that there is a significant difference between the consumption of ambon banana juice and kiwi juice in reducing hypertension in the elderly.  Discussion: There is a difference between consuming ambon banana juice and kiwi juice in reducing hypertension.